A flexible rechargeable zinc-ion wire-shaped battery with shape memory function. Issue 18 (25th April 2018) - Wang, Zifeng; Ruan, Zhaoheng; Liu, Zhuoxin; Wang, Yukun; Tang, Zijie; Li, Hongfei; Zhu, Minshen; Hung, Tak Fuk; Liu, Jun; Shi, Zicong; Zhi, Chunyi
Abstract : A flexible wire-shaped rechargeable Zn-ion battery with shape memory function was fabricated, delivering decent performances and good recoverability to mechanical deformation. Abstract : The ever-growing development of flexible and wearable electronics boosts the research on flexible and wearable energy storage devices. However, these devices are susceptible to mechanical deformation, leading to inevitable damage and degradation of performances. Herein, we report the fabrication of a smart wire-shaped flexible and rechargeable Zn-ion battery with shape memory function, which enables the battery to restore the shape and energy storage capability against mechanical deformation by the temperature triggered shape memory effect. As an energy storage device, the flexible wire battery delivered a specific discharge capacity of 143.2 mA h g −1 at 1C in aqueous electrolyte and a significantly enhanced cycle life due to the polypyrrole coating on the MnO2 nanocrystallites. Moreover, the performance was well-retained in a polymer gel electrolyte, delivering a specific discharge capacity of 135.2 mA h g −1 at 1C and long cycling stability over 1000 cycles, which could be attributed to the enhanced ionic conductivity and water retention properties offered by the gelatin–borax-based polymeric gel. Additionally, the intriguing mechanical properties of the Nitinol wire endowed the yarn battery with high flexibility upon bending, and it could recover from the deformation upon immersion in 45 °C water multiple times while preserving the electrochemical performances.